JUSTICE IN THE MAQASHID APPROACH AL-SYARI'AH - Ananda, Faisar; Nurasiyah, Nurasiyah; Nasution, Muhammad Hasan (Universitas Islam Negeri Sumatera Utara Medan, 2024)
This article describes the concept of justice from the perspective of Islamic legal philosophy. There are two main formulations of justice in this context: The first view considers justice as a harmony between rights and obligations, which is based on the postulate of